Distinction of African trypanosome species using nucleic acid hybridization - Massamba, N.N.; Williams, R.O. (Cambridge University Press, 1984)
We have performed restriction endonuclease digestion of nuclear DNAs, combined with gel electrophoresis and molecular hybridization to characterize different Trypanosoma brucei brucei stocks and to identify trypanosome species. Cloned DNA complementary to the messenger RNAs (mRNAs) for different variable surface glycoproteins (VSGs) of T. b. brucei stock LUMP 227 was used to examine differences in genomic DNAs from T. b. brucei stocks and from various other trypanosome species. These cDNA reagents differentiated the stocks of T. b. brucei and also distinguished the trypanosome species. Our data also show that a T. b. brucei nuclear DNA fragment used as a probe in molecular hybridization analysis provides an appropriate marker in determining trypanosome species. We have extended our analysis of trypanosome nuclear DNA by developing a simple and rapid spot test, for the identification of trypanosome species, which can be carried out using crude materials such as isolated parasites, infected whole blood and tsetse saliva. The procedure is species-specific, sensitive to the level of 104 organisms and is suitable for use under field conditions. Thus, with appropriate sequences for hybridization, the procedure has obvious applications for the diagnosis of African trypanosomiasis.